MEMBANGUN KERUKUNAN MASYARAKAT MULTIKULTURAL - Ngainun Naim (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
It is important to build the harmony in the livelihood among religious followers in Indonesia continuously. We can appreciate their valuable contribution through thought and real action. The idea of teologi kerukunan and fikih kerukunan has important meaning in daily life. The two concept became the basic of theory to implement the harmonious life in multicultural Indonesia society, both theoretically and practically.